Tuning ultrafast chemical reaction dynamics in photoactive proteins - Bassolino, G (2015)
This dissertation investigates the origins of tunable and efficient photochemistry in three different photoactive proteins, bacteriorhodopsin (BR), rhodopsin (RHO) and green fluorescent protein (GFP). In all cases, significant differences exist between the photoreactivity of model chromophores in solution and in the protein environment, in terms of excited state lifetime and efficiency of the primary photochemical process (opsin proteins) or the type of reaction (excited state proton transfer versus C=C double bond photoisomerisation for GFP). The work presented here investigates for each case to what extent the protein environment is necessary to alter the photochemistry of model chromophores in solution. For GFP and BR steric and electrostatic interactions between the protein pocket and the chromophore are shown to be likely responsible for shaping the excited state surface along which the photoreactions take place. For RHO it is suggested, contrary to current belief, that selection of a reactive ground state conformer might be the main effect generating the observed differences between solution and protein environment. The solution photochemistry of structurally modified retinal protonated Schiff bases, taken as model chromophores for the opsin proteins, is studied with continuous wave irradiation experiments and ultrafast transient spectroscopies. Surprisingly large differences are observed for the isomerisation reaction depending on the starting configuration (trans or cis) of the photoactive double bond. The current model for BR based on the tuning of the excited state barrier encountered along the isomerisation coordinate is expanded to include the changes in selectivity, speed and efficiency observed for a series of all-trans derivatives. For 11-cis, the photoisomerisation in solution is proposed to take place along a barrierless isomerisation coordinate, in contrast with the models currently available in literature. It is suggested that the protein might be discriminating between ground state conformers rather than significantly changing the topography of the reaction coordinate. For GFP, excited state Raman spectra are recorded for the wild-type protein, two mutants and a model chromophore in solution. It is suggested that the high frequency vibrational modes observed in the excited state spectra of the proteins but not of the model chromophore in DMSO are a sign of a tighter chromophore environment that inhibits the photoisomerisation reaction occurring in solution.